2020
DOI: 10.1089/dna.2020.5641
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Roles and Prognostic Value of RNA-Binding Proteins in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a malignancy with relatively high incidence and poor prognosis. RNA-binding proteins (RBPs) were reported to be dysregulated in multiple cancers and were closely associated with tumor initiation and progression. However, an integrated analysis of the roles of RBPs in HNSCC has not been conducted. In the present study, we obtained transcriptome data and corresponding clinical information of HNSCC patients from The Cancer Genome Atlas database and screened out dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In order to show that our prognostic model is superior to other models, we compared the HRGP prognostic signature with three published signatures [19][20][21], all data are from TCGA. As we thought, the cindex of the prognostic signature in this study was 0.684, and the HRGP prognostic signature was higher than the existing autophagy-related prognostic signature (c-index = 0.637), the immune-related gene prognostic signature (c-index = 0.592 ) and the RNA-binding protein-related gene prognostic signature (cindex = 0.57) have higher clinical application value.…”
Section: Comparison With Previously Established Prognostic Signaturesmentioning
confidence: 99%
“…In order to show that our prognostic model is superior to other models, we compared the HRGP prognostic signature with three published signatures [19][20][21], all data are from TCGA. As we thought, the cindex of the prognostic signature in this study was 0.684, and the HRGP prognostic signature was higher than the existing autophagy-related prognostic signature (c-index = 0.637), the immune-related gene prognostic signature (c-index = 0.592 ) and the RNA-binding protein-related gene prognostic signature (cindex = 0.57) have higher clinical application value.…”
Section: Comparison With Previously Established Prognostic Signaturesmentioning
confidence: 99%
“…RBPs are also associated with the prognosis of HNSCC. 29 Based on the previous experimental results, we speculated that TM4SF19-AS1 might interact with certain RBPs. HNRNPC has been pointed out to demonstrate high expression in HNSCC tissues.…”
Section: Discussionmentioning
confidence: 92%
“…RBM24 was identified as one downregulated gene in the LN metastasis group. Several members of RRM family have been reported to play vital role in cancer metastasis [ 25 , 26 ], and a bioinformatics study based on data from TCGA database suggested RBM24 might be a prognostic-related gene in head and neck squamous cell carcinoma [ 27 ]. But, the role of RBM24 in HSCC has not been expounded yet.…”
Section: Resultsmentioning
confidence: 99%